Contractual Freedom, Legal Certainty, and the Enforceability of Notarial Deeds: A Normative Analysis - Mochammad Erwin Radityo; Gloria Gita Ginting; Muhammad Hirzi Aldivie (Jurnal Multidisiplin Sahombu, 2026)
The principle of freedom of contract is a fundamental doctrine of contract law that allows parties to determine the terms of their agreements within the limits imposed by statutory law, public policy, morality, and good faith. In civil law systems, agreements are commonly formalized through notarial deeds to ensure legal certainty and strong evidentiary value. This study employs a normative legal approach by examining legislation, legal doctrines, and the regulatory framework governing notarial practice. The findings indicate that a notarial deed attains authentic status only when it complies with the formal and procedural requirements prescribed by law. However, its evidentiary authority does not validate agreements that suffer from defects of consent, lack of legal capacity, unlawful objects, or illegal causes. Such agreements remain subject to judicial review and may be declared void or voidable. This study concludes that freedom of contract and the legal enforceability of notarial deeds are complementary concepts: contractual autonomy governs the formation of agreements, whereas notarial deeds strengthen legal certainty without legitimizing contracts that violate substantive legal requirements.